Applications of a liquid membrane in Taylor flow regime (LMTF) on separation processes and design of fermentation hybrid systems (2019)
In this book, it is shown a proof of concept and the performance assessment of a novel liquid membrane in Taylor flow applied to the lactic acid (LA) removal. Liquid-liquid equilibria (LLE) of potential membrane phases for LA removal were experimentally measured and a LLE model is proposed to fit the values of the of the distribution coefficient and chemical equilibrium constants for this kind of systems. Additionally, molecular toxicity tests of the potential liquid membranes on the lactic acid bacteria Lactobacillus casei ATCC 393 were carried out in order to have a membrane phase for LA removal with a good compromise between a high value of the chemical equilibrium constant and a relatively low molecular toxicity. The performance of the liquid membrane in Taylor flow (LMTF) in terms of hydrodynamics and mass transfer was tested for LA removal. The LA removal is favored at low injection times and high droplet velocities by providing the suitable space-time to achieve the mass transfer at the operating conditions used. A semi-empirical model for calculation of the overall volumetric mass transfer coefficients (OVMTC) was developed and their empirical parameters were fitting by using the experimental results. The LMTF was integrated with a batch lactic acid fermentation in order to remove the LA during fermentation. This hybrid process was experimentally assessed in terms of LA productivity and yields comparing it with a conventional batch fermentation. The LA produced increases by 41%, the glucose consumption increases by 68% and the biomass production increases by 12%. The glucose consumption is higher than LA and biomass production, which is in agreement with the effect of the membrane phase on Lactobacillus casei ATCC 393 which promotes the glucose consumption instead of biomass and LA production. The model for the hybrid process was developed using material balances and the model of the OVMTC of the LMTF for LA removal. The model shows some slight differences as compared with experimental results because the model does not take into account the toxicity effects of the membrane phase on the lactic acid bacteria. In the model is included a LMTF system with multi-channels. The effect of the number of channels of theLMTF is modeled and its impact on productivity, fermentation time, and final biomass concentration are analyzed. From the experimental results, it can say that the LMTF is a promising technology for removal of LA, from both aqueous lactic acid solutions and fermentation broths. The LMTF can be integrated with fermentation processes to remove metabolites and enhance both LA and biomass productivity, however molecular toxicity issues could reduce LA to glucose yield. Within this book, every section of each chapter is self-contain and can be read independently (Texto tomado de la fuente)